CONDITIONS AND PRINCIPLES OF FORMING A SYSTEM OF STRATEGIC MONITORING OF INVESTMENT ACTIVITIES OF FOOD ENTERPRISES - KHUTAK, Arthur Shir (Herald of Khmelnytskyi National University. Economic sciences, 2024)
An essential component of managing any entity's investment activities is monitoring and controlling the investment process based on a particular system of criteria and evaluation indicators. Monitoring and controlling investment activities are necessary for managing the processes of attracting investments, supporting the project implementation process, and post-project support for the functioning of the applicant enterprise and the activities of investors based on an assessment of the project implementation results. The information obtained in the monitoring process makes it possible to improve the investment process, provide a deeper understanding, and increase enterprises' investment attractiveness.In the system of strategic investment management of food enterprises, it is necessary to form an adaptive subsystem of monitoring and control, which would allow them to interact with investors in a mutually beneficial way and to seek opportunities to increase the efficiency of all participants in the investment process. That is, the monitoring system should not only be a tool in the hands of top management, but it should also cover all levels of the enterprise and be integrative, that is, one that can, if necessary, be integrated with the investor's monitoring system, use the same tools and coordinate the results to make mutually beneficial investment decisions. At each level of the enterprise, each participant in the investment process must understand their functions, tasks, and results. At the same time, their work must be coordinated and coordinated. These tasks require the formation of a neutral (objective) information and analytical system of project management, which will allow us to form the most complete picture of the course of the investment process and to invent the most effective ways of cooperation between participants.
Keywords: strategic monitoring; investment activity; food enterprises; food complex; project